Effect of second harmonic in pulse-width-modulation-based DAC for feedback of digital fluxgate magnetometer. (7th March 2018) - Belyayev, Serhiy; Ivchenko, Nickolay
Abstract: Digital fluxgate magnetometers employ processing of the measured pickup signal to produce the value of the compensation current. Using pulse-width modulation with filtering for digital to analog conversion is a convenient approach, but it can introduce an intrinsic source of nonlinearity, which we discuss in this design note. A code shift of one least significant bit changes the second harmonic content of the pulse train, which feeds into the pick-up signal chain despite the heavy filtering. This effect produces a code-dependent nonlinearity. This nonlinearity can be overcome by the specific design of the timing of the pulse train signal. The second harmonic is suppressed if the first and third quarters of the excitation period pulse train are repeated in the second and fourth quarters. We demonstrate this principle on a digital magnetometer, achieving a magnetometer noise level corresponding to that of the sensor itself.